The first elateroid beetles (Coleoptera: Polyphaga: Elateroidea) from the Upper Jurassic of Australia - Oberprieler, Rolf G.; Ashman, Lauren G.; Frese, Michael; Ślipiński, Adam (Zootaxa, 2016)
The first elateroid fossils from the Upper Jurassic Talbragar Fish Bed in Australia are described and illustrated. Wongaroo amplipectorale gen. et sp. n., based on two specimens, is placed in the family Cerophytidae due to its convex, posteriorly weakly angled and laterally carinate pronotum obscuring the head in dorsal view, its relatively long, pointed elytra and slender legs, its 9-striate elytra with deep basal pits and the absence of metacoxal plates. Beattieellus jurassicus gen. et sp. n., described from one specimen, possesses the acutely angled pronotum without a carina on the posterolateral angles and the ventral click apparatus typical of Eucnemidae and is classified in this family. Assignment of it to a eucnemid subfamily is impossible because of the insufficient preservation of relevant characters in the fossil. Four other elateroid fossils, possibly representing eucnemids and elaterids, are illustrated and briefly described but not named, due to their insufficient preservation. These fossils represent the first of their kind in Australia and in the Southern Hemisphere, and Beattieellus is also the oldest eucnemid fossil known and extends the fossil record of Eucnemidae into the Upper Jurassic. The discovery of elateroid fossils in the Talbragar Fish Bed adds to the coleopteran diversity of this ancient lake ecosystem, indicating that it was well wooded and provided suitable habitats of rotten wood for the development of the larvae of these taxa.